Chronic hepatitis type B in childhood: longitudinal study of 35 cases. Issue 6 (June 1981) - Bortolotti, F; Cadrobbi, P; Crivellaro, C; Bertaggia, A; Alberti, A; Realdi, G
Abstract : Clinical, virological, and histological features of hepatitis B virus infection have been examined in 35 children, aged 1 to 11 years, known to be hepatitis B surface antigen (HBsAg) carriers for at least six months when entering the study. Only 10 patients had a history of acute unresolved hepatitis: in the remaining cases the detection of HBsAg had been an occasional finding. Although 77% of the patients were asymptomatic, all had evidence of hepatic involvement and liver history showed the features of chronic persistent hepatitis in 18 cases and of chronic active hepatitis in 16 cases, with associated cirrhosis in two of them. One patient had only minimal histological changes. A high percentage of children with both chronic persistent and chronic active hepatitis had evidence of active virus replication throughout the observation period. During the follow-up study of one to eight years (mean 3.1 +/- 1.7 years), transaminase levels became consistently normal in five patients with chronic persistent hepatitis, and inflammatory infiltrates disappeared in three of them. However, only one of these children cleared HBsAg from serum. Eleven of 16 patients with chronic active hepatitis received immunosuppressive treatment but only one of them achieved a complete and protracted remission, although active viral replication persisted. On the other hand, two of five untreated patients reached complete remission after two and three years of follow-up respectively and one of them cleared HBsAg three years later. These results would suggest the possibility of a spontaneous complete remission of HBsAg positive chronic active hepatitis in children but also raise doubts about the usefulness of immunosuppressive therapy in such patients.